Misconceptions about aerobic and anaerobic energy expenditure - Scott, C. (Journal of the International Society of Sports Nutrition, 2005)
The measurement of gas exchange has played an invaluable role in metabolic interpretation. The uptake of 1 liter of oxygen is often converted into an energy expenditure estimate of 21.1 kilojoules (e.g., 1 L O2 = 21.1 kJ or ~5 kcal). This article demonstrates both the importance of such a conversion and the potential for misinterpretation. Oxygen uptake during heavy and severe exercise will also be discussed.